A new bond slip model for reinforced concrete structures: Validation by modelling a reinforced concrete tie. Issue 7 (5th October 2015) - Mang, C; Jason, L; Davenne, L
Abstract : Purpose: – The purpose of this paper is to present a new bond slip model for reinforced concrete structures. It consists in an interface element (3D) which represents the interface between concrete (modeled in 3D) and steel, modeled using 1D truss elements. Design/methodology/approach: – The formulation of the interface element is presented and verified through a comparison with an analytical solution on an academic case. Finally, the model is compared with experimental results on a reinforced concrete tie. Findings: – Contrary to the classical perfect or "no-slip" relation which supposes the same displacement between steel and concrete, the proposed model is able to reproduce both global (force-displacement curve) and local (crack openings) results. Originality/value: – The proposed approach, applicable to large-scale computations, represents a valuable alternative to the no-slip relation hypothesis to correctly capture the crack properties of reinforced concrete structures.